MetalAfrica: from dream to reality - (:unkn) unknown (My University, 2014)
At SAfA 2012 in Toronto, the concept of MetalAfrica was presented by Caroline Robion-Brunner, the founder and president of this new association. She outlined the scope of MetalAfrica, as an open and easily accessible online platform, including a database, discussion group and blog aimed at providing a virtual community space for those researching metallurgy across the African continent. MetalAfrica was described as a facilitator of academic exchanges and collaborations between researchers from different institutions and countries working on the subject of African metallurgy, with one of its fundamental purposes, in addition to data sharing and accessibility, being to encourage networking and partnerships between the global communities of researchers including PhD students, junior and senior academics. It was proposed that the future widespread use of MetalAfrica will increase the diffusion of scientific knowledge and stimulate academic discussions, for example through publications and conferences. Comments and questions were on the whole positive and encouraging, with more than a hint of scepticism at such an enormous task.Throughout 2013 a team of people gathered to create the association and define the basis of the online platform. At the PAA/SAfA meeting in South Africa in 2014 we look forward to presenting the current state of MetalAfrica, including the structure and nature of the organisation, a demonstration of MetalAfrica.org and our plans for the coming years including the first biennial MetalAfrica meeting at SAfA 2016 in Toulouse. We will be providing early access to the website for those interested, and importantly gaining feedback based on this presentation that will help us as we finalise the format of the organisation and online platform.
Keywords: African Research